Alwx Rider : Never Say Die - Book 11 - Horowitz, Anthony 1955- (New York, NY : Philomel Books, 2017)
Fifteen-year-old MI6 agent Alex Rider travels around the world on a dangerous mission to destroy the deadly terrorist organization, Scorpia, once and for all.
Keywords: Spy stories; Terrorism -- Juvenile fiction; Spies -- Fiction; Terrorism -- Fiction; Adventure and adventurers -- Fiction; JUVENILE FICTION / Action & Adventure / Survival Stories; JUVENILE FICTION / Law & Crime